Ruído emitido por um trator de rabiça em operação de preparo de solo - Silva, Marcio Porfirio da (2019)
Many factors contributed to mechanization in agriculture, such as the pursuit of r educed human effort and increased productivity. For small producers who can not acquire and usually do not need machinery that demands a lot of power in their operations, the use of rabies tractors becomes more present, as a way of not compromising financi al resources, and being a source powerful traction. The use of the bulldozer involves an arduous work in its operation. The operator is exposed to extreme conditions such as temperature, humidity, noise and vibration. Regulatory Standard 15 (NR 15) in its Annex I defines the limits of tolerance for continuous and intermittent noise, the criterion used corresponds to a dose of 100% for exposure at the level of 85 dB for 8 hours daily. Thus, the present study aimed to evaluate the noise levels emitted by a bu lldozer in soil preparation, using the rotating hoe, with and without the coupling of the encanteerador, in two working marches (2nd and 3rd) and in two rotor rotations (256 and 520 rpm). This research was developed in the experimental area belonging to th e Laboratory of Agricultural Machinery Accidents (LIMA), linked to the Department of Agricultural Engineering (DENA) at the Federal University of Ceará (UFC), Pici campus in Fortaleza. The experimental design was completely randomized (DIC), in the factori al scheme of 2x2x2, the operation performed with the hoe with and without the coupling of the dozer, 2 work marches (2nd and 3rd), corresponding to the velocities of 1.6 and 2.1 km h 1 respectively, and two rotator hoe rotor speeds (265 and 520 rpm). When the feeder is mounted to the rotary hoe the noise level is higher in all combinations of rotor travel and rotation due to the increased p ower demand for the operation. It was verified that the values of noise emitted are above 85 dB (A) in all the treatments studied, which is recommended by the NR 15 as the level in which it would not affect the health of the worker, showing that the oper ation with the tractor under the conditions studied does not offer safe conditions for the operator with a daily work load of 8 hours, being indispensable the use of ear protectors during the operation.